2014
DOI: 10.1038/bjc.2014.195
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of two dosing schedules of volasertib (BI 6727), an intravenous polo-like kinase inhibitor, in patients with advanced solid malignancies

Abstract: Background:Polo-like kinase 1 (Plk1) has an important role in mitosis. Volasertib (BI 6727), a potent and selective cell cycle kinase inhibitor, induces mitotic arrest and apoptosis by targeting Plk; this phase I study sought to determine its maximum tolerated dose (MTD) in Asian patients with advanced solid tumours.Methods:Patients were enrolled simultaneously into two 3-week schedules of volasertib: a 2-h infusion on day 1 (schedule A) or days 1 and 8 (schedule B). Dose escalation followed a 3+3 design. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 20 publications
2
54
0
Order By: Relevance
“…We expected treatment efficacy of our triple-labelled siPLK1-StAv-SPIONs based on the ability of PLK1 suppression to prevent tumour cell proliferation by arresting the cells in the G2/M phase of mitosis. 7 22 23 siPLK1-StAv-SPIONs treatment resulted in a pronounced increase in the number of cells in G 2 /M phase comparable to the selective PLK1 inhibitor, BI6727, employed in phase I and II cancer trials 24 and proved to be efficient in silencing of PLK1 in tumour cells ( figure 1E). To further confirm the silencing efficacy of siPLK1-StAv-SPIONs, we performed BrdU proliferation assay and found a significant suppression of proliferation in 6606PDA cells over a period of 48 h (figure 1F).…”
Section: Resultsmentioning
confidence: 93%
“…We expected treatment efficacy of our triple-labelled siPLK1-StAv-SPIONs based on the ability of PLK1 suppression to prevent tumour cell proliferation by arresting the cells in the G2/M phase of mitosis. 7 22 23 siPLK1-StAv-SPIONs treatment resulted in a pronounced increase in the number of cells in G 2 /M phase comparable to the selective PLK1 inhibitor, BI6727, employed in phase I and II cancer trials 24 and proved to be efficient in silencing of PLK1 in tumour cells ( figure 1E). To further confirm the silencing efficacy of siPLK1-StAv-SPIONs, we performed BrdU proliferation assay and found a significant suppression of proliferation in 6606PDA cells over a period of 48 h (figure 1F).…”
Section: Resultsmentioning
confidence: 93%
“…Volasertib has also been tested in clinical trials in solid malignancies, in which the most common dose-limiting effects are thrombocytopenia and neutropenia. 40,41 These problems may be due to specific effects in progenitors cells or that Plk1 inhibitors can inhibit other kinases at specific doses. 42,43 However, our conditional knockout model suggests that Plk1 inhibition actually leads to defective polyploidization and cell death in megakaryocytes, a result with implications in the design of therapeutic protocols targeting this mitotic kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Among three confirmed partial responses, there was one patient with advanced urothelial carcinoma who achieved a prolonged progression free survival of 403 days. Another phase I study of volasertib in Asian patients also showed one partial response in a patient with metastatic ureteral urothelial carcinoma [82]. A phase II study evaluated the efficacy and safety of single-agent volasertib as second-line treatment for advanced urothelial cancers, a patient population without standard therapeutic options [83].…”
Section: Polo-like Kinasementioning
confidence: 99%